New Ostracoda Species in the Upper Part of the Tanjero Formation (Late Maastrichtian), Sulaimaniyha City, Kurdistan Regin-NE- Iraq - Taha, Zardasht Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2020)
The present work is focused on the ostracoda study from the upper part of the Tanjero Formation (Late Maastrichtian), Qlyassan area, Sulaimaniya city, Northeasten Iraq. The Tanjero Formation in Qlyassan section (5 m thick) consists of brownish grey to dark gray marl to silty marl with thin graded sandstone, more than one hundred specimens picked up, fourteen species from nine genera of ostracods were identified and illustrated in the upper unit of the Tanjero Formation. Three new species from the fourteen identified species are recognized which are Cytherella sulaimaniensis sp. nov., Cardobairdia tanjeroiensis sp. nov. and Pontocyprella qlyasaniensis sp .nov. These three new species support the age of the Tanjero Formation as the Late Masstrichtian (Upper Cretaceous).
Keywords: Ostracoda, New Species; Upper Cretaceous (Maastrichitian); Tanjero Formation; Sulaimaniya City; Northeast Iraq